Body, self, other : the phenomenology of social encounters - Dolezal, Luna; Petherbridge, Danielle (Albany, New York : Suny Press, 2017)
Examines the lived experience of social encounters drawing on phenomenological insights.
Agoraphobia and the Look -- Notes -- References -- 13 Intercorporeal Expression and the Subjectivity of Dementia -- Introduction -- Intercorporeal Capabilities -- Constitutive Intercorporeality -- Intercorporeality as a Relation of Expression -- Situated Expression -- Conclusion -- Acknowledgments -- Notes -- References -- Notes on Contributors -- Index.
Includes bibliographical references at the end of each chapters and index.
Description based on print version record.
JSTOR
Keywords: Interpersonal relations -- Philosophy; Other (Philosophy); Phenomenology; Altérité.; Phénoménologie.; phenomenology; PHILOSOPHY / Movements / Phenomenology; Interpersonal relations -- Philosophy; Other (Philosophy); Phenomenology